PEMBANGUNAN NEGARA DI DAERAH PERBATASAN (STUDI PELAYANAN KESEHATAN PUSKESMAS TANJUNG BATU KECAMATAN KUNDUR KABUPATEN KARIMUN TAHUN 2015) - Della Oktavia; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
In the Development of Border Area State, Karimun Regency is directly adjacent to Malaysia and Singapore. Health services in Kecamatan Kundur seen experiencing problems in health services that are not optimal in providing satisfaction services to patients, the lack of health personnel, facilities and infrastructure so that a constraint in health services. The purpose of the study is first, to describe how the institutional capacity in implementing health services in Kundur subdistrict. Second, to determine whether the strength dimension (Strength) and its scope or scope (Scope) based on the steat building framework in supporting health services. The type of research used is descriptive qualitative research method. The location of this research was conducted at Puskesmas Tanjung Batu Kundur sub-district Karimun regency. Technique of data collecting done by doing observation, interview, and documentation. Based on the results of the study, the authors draw the conclusion that in the Institutional Capacity in Health Services has not run optimally because of the health side of the lack of skill in the field of expertise and equipment of health facilities and infrastructure are not adequate. And in the Strength and Scope dimensions, it can be seen from the functions of the State that for minimalist function, the minimum is not fulfilled, such as the availability of pharmaceutical stock, the medical device becomes an obstacle in terms of health needs.Keywords: State Building, Health Service, Karimun District Health Office